2015
DOI: 10.3102/0002831214565788
|View full text |Cite
|
Sign up to set email alerts
|

Year One Results From the Multisite Randomized Evaluation of the i3 Scale-Up of Reading Recovery

Abstract: Reading Recovery (RR) is a short-term, one-to-one intervention designed to help the lowest achieving readers in first grade. This article presents firstyear results from the multisite randomized controlled trial (RCT) and implementation study under the $55 million Investing in Innovation (i3) Scale-Up Project. For the 2011-2012 school year, the estimated standardized effect of RR on students' Iowa Tests of Basic Skills (ITBS) Total Reading Scores was .69 standard deviations relative to the population of strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The context for the present research was Reading Recovery, a literacy intervention for struggling first‐grade students (see May et al., ). We collected 20 videos from 10 teachers and 85 of their students as they read a new, unfamiliar book to their teacher.…”
Section: Insights From a Recent Scaffolding Studymentioning
confidence: 99%
“…The context for the present research was Reading Recovery, a literacy intervention for struggling first‐grade students (see May et al., ). We collected 20 videos from 10 teachers and 85 of their students as they read a new, unfamiliar book to their teacher.…”
Section: Insights From a Recent Scaffolding Studymentioning
confidence: 99%
“…There are research results showing that RR meets the needs of some students (e.g. Pinnell et al., ; D'Agostino & Murphy, ; Schwartz, ; U.S. Department of Education, What Works Clearinghouse, 2007, 2013, 2014; May et al., ; D'Agostino & Harmey, ; D'Agostino et al., ; Shanahan, ). Many studies and reviews, however, cast considerable doubt on the effectiveness of the programme (e.g.…”
Section: The Goals Of Reading Recoverymentioning
confidence: 99%
“…A US$55 million ‘scale‐up’ study funded mostly by the US Department of Education as part of the 2010 Obama administration economic stimulus package, involved more than 1400 schools with targeted assistance for over 88,000 students. The authors of the study (May et al., ) described a two‐tier process for selecting students into the RR programme. They drew attention to the requirement of the RRCNA Standards and Guidelines (Reading Recovery Council of North America, ) that schools select ‘the lowest achieving first‐grade students'and serve the ‘lowest scorers first’ (May et al., , p. 24).…”
Section: Does Reading Recovery Always Select the Lowest Achieving Chimentioning
confidence: 99%
See 1 more Smart Citation
“…This variability was in READING RECOVERY: An Evaluation of the Four-Year i3 Scale-Up | 15 May, 2015) Percent ELL large part due to the significant differences in regional early-literacy infrastructures. We found that several regions enjoyed significant state-level political support for Reading Recovery and early-literacy programming.…”
Section: Recruitment Strategies: Varied and Context-drivenmentioning
confidence: 99%